The system of appointment of heads of educational inspection and its impact on its governance - Gomila i Benejam, Josep (Avances en Supervisión Educativa, 2024)
This article aims to analyze the real functioning of the System for appointing the main people responsable for the educactional inspection and see the impact that these procedures have on its governance. Likewise, it aims to formulate specific proposals to guarantee the suitability of the people who exercise these responsabilities, with the aim of improving their effectiveness and being able to better respond to the challenges that the educational inspection of the futur has.